(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The legal and political structures that govern interactions within a society and between thatsociety and others are collectively referred to as government. These organizations are vested with theresponsibility of determining the best course of action for the preservation of social order and theattainment of predetermined societal goals. The degree to which a government is unconstrained andunchecked determines how much power it has over its own populace. The human and material means bywhich a state can back its foreign policy determines the extent to which it can exert influence overseas.There has always been a wide spectrum of governmental structures, from the first ad hoc groups likeclans and tribes to the modern global superpowers and international governments. Until quite recently,certain governments were powerful enough to build empires, over which they exerted control not justover their own people but also over those of other states, despite differences in geography, culture, andlanguage. Before India won its independence from British imperialism, it was a colony of the UnitedKingdom. The modern Indian administration owes much to the influence of the British Empire. India’sfounding document, the Constitution of India, has its origins in the Government of India Act of 1935.